Design of traction battery pack for battery electric vehicle - Low, Kelvin Zhi Wei (2015)
This report primary serves to document the design process for the development of a traction battery pack for an electric vehicle, Nanyang Venture VII. There are four key elements in a vehicular battery module: enclosing structure, energy storage element, temperature control system and lastly the safety and information consolidation systems. The process begins with a conceptualisation process to derive suitable solutions to the functions of a traction battery. The concepts are evaluated and further developed through embodiment of design processes. Next, the systems are integrated in the detailed design process and enhanced with engineering calculations to optimise function and utility. Finally, the fabrication steps are presented and detailed.